Home ranges and hatching success of threatened Eurasian curlew in north-eastern Europe relates to habitat type: Natural vs. agricultural landscapes - Bocher, Pierrick; Donnez, Marie; Chenu, Audran; Sviridova, Tatiana; Fort, Jérôme; Garthe, Stefan; Jiguet, Frédéric; Piha, Markus; Elts, Jaanus; Marja, Riho; Amélineau, Françoise; Robin, Frédéric; et al. (Elsevier, 2024)
Farmland birds are among the most threatened species in Europe, largely as a result of the intensification of agriculture leading to widespread biodiversity losses. Ground-breeding shorebirds in grassland and arable habitats are particularly exposed to human threats and predation in highly modified landscapes; however, parts of their populations still breed in natural habitats and could provide a reservoir for threatened populations. This study aimed to improve our knowledge of the spatio-temporal use of breeding habitats by Eurasian curlew Numenius arquata arquata in a core area of the population in remote north-eastern Europe. A total of 83 adult birds across Europe were tagged with GPS devices between 2014 and 2022 to analyse their home-range sizes, habitat use and hatching success. Birds were distributed at breeding sites from 52°N to 66°N between Finland and the Ural Mountains. Forty-one percent of individuals nested in bogs, 33% in grassland, and 20% in abandoned farmland. Birds nested predominantly in bogs at northern latitudes and in grassland at southern latitudes, while abandoned farmland was mainly used at intermediate latitudes. The mean home range was largest for birds breeding predominantly in grassland while birds in bogs had the highest hatching success rate. Russia and Finland host the core population of the subspecies N. a. arquata during breeding period, which is essential for preserving the species on a European scale. Their survival may depend on well-preserved bogs and the maintenance of grassland areas, given that large areas of abandoned farmland are destined to become either forest or to be reclaimed for cereal crops or fodder grass in the short and medium terms. Given the large breeding populations in both countries, Russia and Finland have major responsibilities to maintain these essential populations on a biogeographical scale.
Keywords: meadow bird; grassland; abandoned farmland; natural afforestation; bog; GPS-tracking